Variation in Lipid Peroxidation in the Ejaculates of Wild Banded Mongooses (Mungos mungo): A Test of the Oxidative Shielding Hypothesis - Graham Birch; Magali Meniri; Chris Mitchell; Francis Mwanguhya; Robert Businge; Solomon Ahabyona; Hazel J. Nichols; Michael A. Cant; Jonathan D. Blount (MDPI AG, 2024)
Reproductive activity is costly in terms of future reproduction and survival. Oxidative stress has been identified as a likely mechanism underlying this cost of reproduction. However, empirical studies have yielded the paradoxical observation that breeders often sustain lower levels of oxidative damage than non-breeders. The oxidative shielding hypothesis attempts to explain such data, and posits that breeders pre-emptively reduce levels of oxidative damage in order to protect their germ cells, and any resultant offspring, from harm caused by exposure to oxidative damage. While there is some empirical evidence of oxidative shielding in females, there have been no explicit tests of this hypothesis in males, despite evidence of the oxidative costs to the male reproductive effort and the vulnerability of sperm cells to oxidative damage. In this study, we assess lipid oxidative damage (malondialdehyde, MDA) in the ejaculates of reproducing and non-reproducing wild banded mongooses. We found that, among breeding males, ejaculate MDA levels were lower during mate competition compared to 2 months later, when individuals were not mating, which is consistent with the oxidative shielding hypothesis, and similar to findings in females. However, ejaculate MDA levels did not differ significantly between breeding and non-breeding individuals at the time of mating, contrary to expectation. The finding that ejaculate MDA was not higher in non-breeders may reflect individual differences in quality and hence oxidative stress. In particular, breeders were significantly older than non-breeders, which may obscure differences in oxidative damage due to reproductive investment. Further research is needed to establish the causal relationship between reproductive investment and oxidative damage in ejaculates, and the consequences for offspring development in banded mongooses and other species.